PENGARUH DISIPLIN BELAJAR, MOTIVASI BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SMA MUHAMMADIYAH KOTA PAGAR ALAM - Firman Feriza (UIN Fatmawati Sukarno Bengkulu, 2020)
The purpose of this study is to determine: 1) Learning Discipline has a direct positive effect to learning achievement.2) Learning Motivation has a direct positive effect to learning achievement. 3) Family environment has a direct positive effect to achievement. 4) Learning Discipline, Learning Motivation, and Family Environment together have a direct positive effect to learning achievement. This research used quantitative approach which data and information in formof numerical, whereas research type is Compositional Causal and Ex Post Facto. The population was 239 students, while the sample was 36 students (15%) of the population. Technique for collecting the data used questionnaires and documentation. The result of this study:1) The discipline of learning has a direct positive effect to the learning achievement of 0.112 (11.20%). 2) Motivation to learn does not give effect to learning achievement equal to -0.333. 3) The family environment does not affect the learning achieve- ment of -0.059 4) Learning discipline, motivation in learning, and family environment gave direct positive effect to learning achievement of 0151 (15.10%).